If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + 3x = 2 + 5x + 5 Reorder the terms: 14 + 3x = 2 + 5 + 5x Combine like terms: 2 + 5 = 7 14 + 3x = 7 + 5x Solving 14 + 3x = 7 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 14 + 3x + -5x = 7 + 5x + -5x Combine like terms: 3x + -5x = -2x 14 + -2x = 7 + 5x + -5x Combine like terms: 5x + -5x = 0 14 + -2x = 7 + 0 14 + -2x = 7 Add '-14' to each side of the equation. 14 + -14 + -2x = 7 + -14 Combine like terms: 14 + -14 = 0 0 + -2x = 7 + -14 -2x = 7 + -14 Combine like terms: 7 + -14 = -7 -2x = -7 Divide each side by '-2'. x = 3.5 Simplifying x = 3.5
| 7x+8x=45-90 | | 6x+3=-45-2x | | 5(3x-2)=35+45 | | 2(h-1)=3(h+1) | | (2x-7/12)+x=(2x+7/2)+3 | | 5x^2+7x+95=0 | | .3333(5x-8)=3 | | y=2x+22/5 | | onethird(5x-8)=3 | | 5y=2x+22 | | -4x+13-2x=3x-11 | | 2x-5/3+5=8 | | -9m+m^2=0 | | (11b+9)(2b-3)=0 | | 2(x-7)-1=5(3x+1) | | 3x/5+2x=0 | | (t/8+5)=7 | | x=3x+7(x-8) | | -8=4(9-2)+4 | | 3x-x/8=30 | | 7-3r=r-4(5-2/5r) | | 6=4/5+5 | | -13=h-1 | | 0-4x+7=11 | | g(t)=3t-3 | | 2.8=6/4 | | f(x+8)=(x+8)2-3(x+8)-2 | | 0.3x^5+0.4x^4-8x^3-7x^2+23x+22=0 | | 3g-4=7g+12 | | 15=3n/5 | | -3/4+3=-12 | | 2p=5y |